A preliminary investigation of high retinoic acid exposure during fetal development on behavioral competency and litter characteristics in newborn rats - Swann‐Thomsen, Hillary E.; Mendez‐Gallardo, Valerie; Kollmeyer, Leah R.; Hunter, Kira; Brumley, Michele R. (Brain and behavior, 2021)
Myelomeningocele (MMC) is the most common and severe type of spina bifida in which the developing spine and neural tube fail to close during prenatal development. This typically results in a small portion of the lower spinal cord and meninges protruding from the back of the individual, accompanied by severe motor and sensory deficits. In rats, retinoic acid (RA) exposure in high doses during fetal development has been shown to induce morphologic and clinical symptoms similar to humans with MMC. The aim of the current study was to examine litter characteristics and sensorimotor function in MMC‐affected rat pups. Pregnant rats were gavage‐fed 2 ml olive oil or all‐trans RA (40, 45, 50 mg/kg) on gestational day 11. Pups underwent behavioral testing on postnatal day 2. Litter characteristics and newborn sensorimotor function varied across RA doses. Pups prenatally exposed to 45 and 50 mg/kg RA weighed significantly less than olive oil and 40 mg/kg RA pups. Litters exposed to 45 mg/kg RA suffered significantly higher mortality rates compared to other groups. Additionally, bladder function was significantly impaired in pups exposed to 40 mg/kg RA. Sensorimotor function findings demonstrated that for most behavioral assessments there was not a significant difference between control and RA‐exposed subjects. However, pups treated with 40 mg/kg RA showed increased facial wiping, suggesting a hyper‐responsiveness to sensory stimuli. Overall, the findings of the current study provide evidence for a model to examine litter characteristics and behavioral effects as well as morphology.